Characterization of nanocoolant for improving cooling channel design in hot press forming - Yusoff, A. R.; Azmi, W. H.; Hamedon, Zamzuri B.; Saptaji, Kushendarsyah; Osman Zahid, Muhammed Nafis; Shaharudin, Mohd Ali Hanafiah (2018)
Hot press forming (HPF) to develop ultra-high strength steel (UHSS) of boron sheet metals for vehicle inner body panels offers efficient fuel consumption in order to reduce carbon dioxide gas emissions by weight reduction and improves passenger safety because of its high mechanical properties. To strengthen a UHSS material such as boron steel, it is required to manufacture from HPF process. The sheet metal is heated up to austenitic temperature and then rapidly quenched in an enclosure dies at a certain holding time to exhibit martensitic transformation phase. In the HPF process, a similar die is used as in the cold stamping operation, but with the additional cooling channel. Currently, water is used as coolant in the HPF process to quench boron steels in a closed die with a cooling channel. However, to enhance the performance of HPF dies and increase the mechanical properties of hot pressed boron steel, the fluid with better thermal properties will be used instead of normal water. During the quenching operation, an optimum cooling rate and homogeneous temperature distribution on hot blanks towards the achievement of the martensitic microstructure transformation as well as high mechanical properties. This study dispersed Al2O3 nanoparticles with an average diameter of 13 nm in three volume percentage base ratios of water (W) to ethylene glycol (EG) such as 60%:40%, 50%:50%, and 40%:60% by using the two-step preparation method. The two main parameters in cooling rate performance are thermal conductivity and dynamic viscosity. The nanocoolant of Al2O3/water–ethylene glycol mixture is prepared for the volume concentration range of 0.2 to 1.0%. The thermal conductivity and dynamic viscosity are then measured at a temperature range of 15 to 55 °C. The heat transfer distribution of the heated blanks with nanocoolant and chilled water are determined by experimental analysis of HPF process. It was found that the highest enhancement of thermal conductivity was observed to be 10% higher than base fluid for 1.0% volume concentration at 55 °C in 60%:40% (W/EG). However, the highest enhancement of dynamic viscosity was measured to be 39% for 1.0% volume concentration in 40%:60% (W/EG) at 25 °C. The convective heat transfer coefficient of 1.0%concentration in 60%:40% (W/EG) at 25 °C is enhanced by 25.4% better than that of 50%:50% and 40%:60% (W/EG) base fluid. Therefore, this study recommends the use of Al2O3 in 60%:40% (W/EG) mixture with volume concentration of less than 1.0% for application in cooling channel of HPF dies. It was also evident that the pattern of temperature distribution of the experimental results was in agreement with some researchers. The tensile strength and Vickers hardness values of the hot pressed parts were evaluated to be approximately 1550 MPa and 588 HV, respectively. In conclusion, nanocoolant as cooling fluid with higher convection heat transfer coefficient compared to the chilled water can reduce the cycle time and increase the productivity of HPF process